1989
DOI: 10.1042/bst0170199
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of different isolates of Verticillium on phenylalanine ammonia lyase activity and phytoalexin biosynthesis in tissues of Medicago sativa L

Abstract: It is concluded that the receptor occupancy-response relationship is very similar for insulin and antibodies, in terms of the efficiency of coupling of occupied receptor to the signalling pathway which determines metabolic responses. However, this signalling pathway does not require autophosphorylation of receptors in the case of activation by anti-receptor antibodies. Indeed antibody 25-49 had no detectable effect on receptor phosphorylation in situ, even at a concentration 100 x higher than that required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…A t t h e same t i m e t h e r e is increasing evidence t h a t inositol-1,4,5-trisphosphate ( I n s ( l 4 5)P3) may be responsible f o r t h e release of Ca24 from plant microsomes and vacuoles [l]. Previous work employing [3H]-inositol, has provided provisional identification of 1ns(1,4,5)P in lucerne cell suspension cultures and t h e latelling data obtained is consistent with a role for Ins (1,4,5)P3 in phytoalexin accumulation induced b y fungal elicitor (23. In the studies reported here, binding saturation analysis has been employed t o confirm these earlier findings.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…A t t h e same t i m e t h e r e is increasing evidence t h a t inositol-1,4,5-trisphosphate ( I n s ( l 4 5)P3) may be responsible f o r t h e release of Ca24 from plant microsomes and vacuoles [l]. Previous work employing [3H]-inositol, has provided provisional identification of 1ns(1,4,5)P in lucerne cell suspension cultures and t h e latelling data obtained is consistent with a role for Ins (1,4,5)P3 in phytoalexin accumulation induced b y fungal elicitor (23. In the studies reported here, binding saturation analysis has been employed t o confirm these earlier findings.…”
supporting
confidence: 81%
“…A f t e r 6 days growth t h e lucerne cell-suspension cultures [3] were either used directly o r were challenged by addition of VerticiUium albo-atrum elicitor solution [4] o r an equivalent volume of H20. LiCl (lOpmol/ml cells) w a s added to t h e suspension cultures a t t h e same t i m e as treatment was initiated.…”
mentioning
confidence: 99%
“…After mixing in vortex, 5 µL was injected into HPLC and by the detector recording the chromatogram chart and measuring the retention time. Same technique was used for determination the retention time of the purified cAMP eluted peak (step 3) 25,26 . TLC analysis: A uniform thin layer silica gel G60 has been used as the stationary phase in the project to separated cAMP.…”
Section: Column Chromatography Purificationmentioning
confidence: 99%